Formula Dan Kualitas Nugget Ikan Rinuak - Yuliana Yuliana (JURNAL PENDIDIKAN DAN KELUARGA, 2020)
Rinuak fish is a species of small fish in Lake Maninjau. At the end of 2016 to mid-2018, rinuak fish are threatened with extinction. But at the end of 2018 until now, the catch of rinuak fish in Lake Maninjau is abundant again. Rinuak, including fish species that quickly rot if not processed immediately. So far, the form of rinuak fish processing is still limited. Therefore, it is necessary to develop in the form of processed food products made from rinuak fish, one of which is nuggets. The purpose of this study is to standardize the formula and identify the quality of the rhinoceros fish nuggets. The research conducted was an experiment to get the design of rinuak fish nugget products with a standard recipe. The formula standardization stage is carried out by eight expert validators in the fields of food, food, and nutrition. The results found a standard formula or recipe, which is done through a validation process twice with three trials. The results of rinuak fish nugget quality obtained an average score on the color quality categorized quite good, the shape quality was categorized quite good, the aroma quality was categorized very good, the texture quality was categorized good (soft and savory), and the taste quality was categorized good (tasty and delicious)